“SMART KIDS’ ENGLISH CORNER”: FACILITATING YOUNG LEARNERS IN A RURAL AREA TO LOVE ENGLISH - Subekti, Adaninggar Septi; Kriswandi, Queen Alfa Milka; Sutanto, Velline Gisella; Rafjanza, Richard Alvin; Premono, Katharina Winahyu; Alvinio, Arka Jedidian; Sujanto, Matthew Alexander (GERVASI: Jurnal Pengabdian kepada Masyarakat, 2025)
Given the importance of English proficiency in the era of globalization and the limited exposure to English in rural communities, a training program entitled “Smart Kids’ English Corner” was designed to empower young learners aged 5 to 12 years in the village of Tapen, Argosari, Sedayu, Bantul, Yogyakarta. The program consisted of four sessions conducted in July 2025. It provided opportunities for learners to practice introducing themselves and their parents, naming colours and shapes, naming fruits and vegetables, and expressing themselves using basic English. A total of 27 learners participated and practiced spoken English in a relaxed and enjoyable atmosphere. Overall, the program aimed to foster a positive attitude and early interest in learning English, with the expectation that participants would develop an optimistic view toward the language. Despite several limitations, such as the limited relevance of some learning activities, the program can be considered successful, as the participants appeared to enjoy each learning moment throughout the sessions.